Effect of Green Tea Aqueous Extract on Body Weight, Glucose Level, and Kidney Functions in Diabetic Male Albino Rats - Al-Hilfy, Jabber H Yenzeel (Al-Nahrain Journal of Science, 2012)
The effect of daily oral doses of green tea water extract for 4 weeks on body weight, plasma glucose level, kidney functions in alloxan-induced diabetic rats was investigated. Forty adult male albino rats (150 -160 g) was divided into 4 experimental groups: The first group was considered as control group. The second group was treated with water extract of the green tea (200 mg/kg b.w).The third group was infected by induction of experimental diabetes by intraperitonial injection of (150 mg/kg b.w) alloxan, and the fourth group was infected by induction diabetes and treated with green tea extract. Different physiological parameters were performed including recording of the body weight and measuring blood sugar, creatinine and urea levels. Body weight loses, plasma glucose, creatinine, and urea levels were significantly (p< 0.05) reduced in diabetic rats treated with green tea when compared with the diabetic rats. From these results, it can be conclude that the consumption of green tea extract produced a significant reduction in glucose level in diabetic rats. In addition, it is capable of improving the impaired kidney functions in diabetic animals.